BOOK REVIEW: Ángeles Caso, “Sissi. Biografia împărătesei Elisabeta de Austro-Ungaria”, Bucureşti: Corint, 2014 - INDRECAN, Vlad-Radu (Studia Universitatis Babeș-Bolyai Historia, 2019)
Ángeles Caso is a spanish journalist, with a degree in Art History. She is also a translator and a writer. Ángeles Caso's work and cultural background should be taken into account: she worked as a journalist for Panorama Regional and for a variety of institutions like Prince of Asturias Foundation, or the Institute Feijoo of 18th century studies. Also, she worked in television at Televisión Española and Cadena SER. Besides the study dedicated to Sissi, she wrote El peso de la sombras (finalist at the Planeta Awards in 1994), El mundo visto desde el cielo. El resto de la vida. Un largo silencio (Fernando Lara award in 2000) and much more. In 2009 she won the Planeta award for the novel Contra el viento. Of course, everybody heard about Elisabeth, the wife of emperor Franz-Joseph. You don't have to be a historian or a journalist in order to know who Sissi was. Nowadays, the majority knows her from the movie Princess Sissi (1955), starring Romy Schneider, or Princess Sissi. The Animated Series, which aired in 1997 on France 3 Channel. And for those of us who are really passionate about the Royal Families of the 19th century, there are lots of historical studies, biographies and memoirs about the life of Elisabeth. Authors like Brigitte Hamann, Egon Caesar Conte Corti, A. de Burgh, George Upton, Allison Pataki or Jean des Cars dedicated works regarding Sissi, some of them verry well documented. Following this statement, a question occurs: where does Ángeles Caso's study stands? Once we open the book, we see that we have to deal with three main parts. The first part of the study is dedicated to Sissi's life (approximately 80 pages of information). The second part is represented by a photo album and the third part contains a variety of poems written by the empress.